Dekomposisi Ensemble untuk Peramalan Harga Bawang Merah DKI Jakarta - Febie Tri Lestari; Farit Mochamad Afendi; Mohammad Masjkur; Budi Waryanto (Xplore: Journal of Statistics, 2019)
Onions are one of the vegetable commodities that are not distributed and included as seasonal crops. Onions are commonly used as cooking spices and traditional medicine. At the time of the religious holidays or non-harvest season, the stock of onions is not able to meet the demand, hence the government has to import them, but that increase the fluctuations of onion prices on the market. Actually, by utilizing the price fluctuation, information about the factors, will be obtained by reviewing the price movement and precise forecasting of the price of onions. Ensamble Empirical Mode Decomposition (EEMD) method can be applied to examine that. EEMD is a decomposition method that can be used to convert a series of time functions from a data signal into several sub-signals resulting from flattening, otherwise known as Intrinsic Mode Function (IMF) and IMF remaining. In this research, this concept applied to data on weekly onion prices in DKI Jakarta from July 2008 to April 2018 as many as 521 data. Based on the results of data processing, as many as 7 IMF and IMF remaining were used as IMF forecasting and the IMF remaining in the future. The forecast was performed by choosing the best model of each IMF component and IMF remaining, used ARIMA. In the end, the weekly price forecast for onion in Jakarta from May - July 2018 ranged from Rp34295.67, - to Rp36133.36, - with average forecasting prices for May-July 2018 amounting to Rp34482.39 - Rp 35207.12 and Rp 36024.88 with a MAPE value of 1.85%.